Alpha-sialon fluorescent powder as well as preparation method and application thereof

By synthesizing the α-Cyron front-drive body powder at low temperature and low pressure, and further sintering under high temperature and high pressure, the problem of being difficult to control the single-phase structure when the alpha-seson fluorescent powder is difficult to control the single-phase structure when it is synthesized at high temperature and high pressure. promote.

CN119331616APending Publication Date: 2025-01-21JIANGSU BREE OPTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411373676.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

It is difficult to control its single-phase structure when synthesized under high temperature and high pressure, resulting in poor luminescence performance.

Method used

By synthesizing α-Sialon precursor powder at low temperature and low pressure, and further sintering it at high temperature and high pressure, the crystals grow, and at the same time, activated ionic compounds are added to solid dissolve them into single-phase α-Sialon.

Benefits of technology

The single-phase composition of α-Sialon phosphor is achieved and its luminescent performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331616A_ABST
    Figure CN119331616A_ABST
Patent Text Reader

Abstract

The invention provides alpha-sialon fluorescent powder and a preparation method and application thereof. The method comprises the following steps: S1, providing silicon nitride, an aluminum source, an M1 source and an M2 source as raw materials according to a stoichiometric ratio composed of a structural general formula M1xM2y (Si, Al) 12 (O, N) 16; s2, mixing the silicon nitride, the aluminum source, the M1 source and part of the M2 source in the raw materials to obtain a first mixture, sintering in an inert atmosphere under the conditions of 1400-1700 DEG C and 0.1-0.5 MPa, and crushing to obtain alpha-sialon precursor powder; and S3, mixing the alpha-sialon precursor powder with the remaining M2 source in the raw materials, sintering in an inert atmosphere under the conditions of 1750-2000 DEG C and 0.55-2 MPa, and crushing to obtain the alpha-sialon fluorescent powder. The alpha-sialon fluorescent powder has good luminescence performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of luminescent materials, and specifically relates to an α-sialon phosphor and a preparation method and application thereof. Background Art

[0002] With the popularity of white light LED lighting and LED display devices converted by phosphor light, the role of phosphor is becoming more and more important. The light efficiency, stability and heat resistance of phosphor have a decisive effect on LED devices, especially with the development of high power and laser lighting, the stability and heat resistance of phosphor are particularly important. Nitride and nitrogen oxide phosphors have inherent advantages in high power and laser lighting due to their stable structure and high heat resistance. Among nitrogen oxide phosphors, there are two types of sialon-type phosphors, one is α-sialon and the other is β-sialon. The emission wavelength of α-sialon phosphor is in the yellow and orange region, and it is mainly used in LED lighting and automotive turn signals, while β-sialon is mainly used in LED displays.

[0003] The composition of α-sialon phosphor is M1 x M2 y (Si,Al) 12 (O,N) 16 Due to its wide composition range, the difference in composition will lead to different coordination environments of the activated ions, resulting in different luminescent energy levels of the activated ions, resulting in differences in luminescent colors and reducing luminescent intensity. Therefore, it is necessary to provide an α-sialon phosphor with high luminescent intensity. Summary of the invention

[0004] In view of this, the present application provides an α-sialon phosphor and a preparation method and application thereof. The α-sialon phosphor has a single-phase composition and has good luminescence performance.

[0005] In a first aspect, the present application provides a method for preparing an α-sialon phosphor, comprising the following steps:

[0006] Step S1: According to the general structural formula M1 x M2 y (Si,Al) 12 (O,N) 16 The stoichiometric ratio of the composition provides silicon nitride, aluminum source, M1 source, and M2 source as raw materials, wherein M1 is selected from at least one of Li, Mg, Ca, Y, Sr, and Gd, and M2 is selected from at least one of Eu, Ce, Pr, Tb, Yb, Dy, and Er, 0.3≤x≤2.0, and 0≤y≤0.1;

[0007] Step S2: mixing silicon nitride, aluminum source, M1 source and part of M2 source in the raw material to obtain a first mixture, sintering the mixture in an inert atmosphere at 1400-1700° C. and 0.1-0.5 MPa, and crushing the mixture to obtain α-sialon precursor powder; wherein the mass of the part of M2 source accounts for less than 50% of the total mass of the M2 source in the raw material;

[0008] Step S3: Mix the α-sialon precursor powder with the remaining M2 source in the raw material to obtain a second mixture, sinter the mixture at 1750-2000° C. and 0.55-2 MPa in an inert atmosphere, and grind the mixture to obtain α-sialon phosphor.

[0009] According to the present application, an α-sialon precursor powder having a single-phase structure is synthesized by adding little or no activating ion compound at low temperature and low pressure, and then the α-sialon precursor powder is crystallized and grown at high temperature and high pressure, and activating ion compounds are added at the same time to dissolve the activating ions into the single-phase α-sialon without affecting its phase composition, thereby obtaining an α-sialon phosphor having a single-phase composition, and thus having good luminescence properties.

[0010] In some embodiments, the aluminum source includes aluminum nitride and / or aluminum oxide, the M1 is Ca, and the M1 source includes calcium nitride and / or calcium carbonate; the M2 is Eu, and the M2 source includes at least one of europium oxide, europium fluoride, europium nitride, europium boride, and europium oxynitride.

[0011] In some embodiments, in step S2: the first mixture also includes a first flux, and the first flux is fluoride and / or chloride.

[0012] In some embodiments, in step S2: the sintering time is 2 to 6 hours.

[0013] In some embodiments, in step S2: the average particle size of the α-sialon precursor powder is 1 to 5 μm.

[0014] In some embodiments, in step S3: the second mixture further includes a second flux, and the second flux is fluoride and / or chloride.

[0015] In some embodiments, in step S3: the sintering time is 2 to 8 hours.

[0016] In some embodiments, in step S3: after the sintering, the temperature is kept at 1300-1600° C. and 0.05-0.1 MPa in a reducing atmosphere for 2-6 hours, wherein the reducing atmosphere is an inert gas with a hydrogen volume percentage of 1%-5%.

[0017] In some embodiments, in step S2: the mass of the portion of the M2 source accounts for less than 30% of the total mass of the M2 source in the raw material; preferably, no M2 source is added to the first mixture.

[0018] In a second aspect, the present application provides an α-sialon phosphor prepared according to the method described in any embodiment of the first aspect.

[0019] In a third aspect, the present application provides a luminescent product comprising the α-sialon phosphor described in any embodiment of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD spectrum of the α-sialon precursor powder in Example 1 of the present application.

[0021] Figure 2 This is the XRD spectrum of the α-sialon phosphor in Example 1 of the present application.

[0022] Figure 3 This is the SEM image of the α-sialon precursor powder in Example 1 of the present application.

[0023] Figure 4 This is the SEM image of the α-sialon phosphor in Example 1 of the present application.

[0024] Figure 5 1 is the emission spectrum of the α-sialon phosphor in Example 1, Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0026] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.

[0027] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0028] The inventors found that: since α-sialon phosphor has a wide composition range and needs to be synthesized under high temperature and high pressure, it is difficult to obtain a single-phase product by direct synthesis. The difference in composition will lead to different coordination environments of the activated ions, resulting in different luminescence energy levels of the activated ions, resulting in differences in luminescent colors and poor luminescence performance.

[0029] In response to the above problems, the related art generally adds a certain amount of pre-synthesized α-sialon phosphor as a seed during the synthesis to reduce the generation of impurity phases during the high temperature and high pressure synthesis process. However, the problem with the above process is that the pre-synthesized α-sialon phosphor is also synthesized under high temperature and high pressure, and it is difficult for it to have a single-phase structure. Therefore, the crystal phase of the α-sialon phosphor further synthesized by using it as a seed is also difficult to control.

[0030] Based on this, the present application proposes an α-sialon phosphor and a preparation method thereof, wherein the method synthesizes a single-phase α-sialon precursor powder at low temperature and low pressure, and then further grows the α-sialon precursor powder as a seed at high temperature and high pressure, thereby obtaining an α-sialon phosphor with a single-phase structure and good luminescence performance. The following is a detailed description through specific implementation methods.

[0031] In a first aspect, the present application provides a method for preparing an α-sialon phosphor, comprising the following steps:

[0032] Step S1: According to the general structural formula M1 x M2 y (Si,Al) 12 (O,N) 16 The stoichiometric ratio of the composition provides silicon nitride, aluminum source, M1 source, and M2 source as raw materials, wherein M1 is selected from at least one of Li, Mg, Ca, Y, Sr, and Gd, and M2 is selected from at least one of Eu, Ce, Pr, Tb, Yb, Dy, and Er, 0.3≤x≤2.0, and 0≤y≤0.1;

[0033] Step S2: mixing silicon nitride, aluminum source, M1 source and part of M2 source in the raw materials to obtain a first mixture, sintering the mixture at 1400-1700° C. and 0.1-0.5 MPa in an inert atmosphere, and crushing the mixture to obtain α-sialon precursor powder; wherein the mass of the part of M2 source accounts for less than 50% of the total mass of the M2 source in the raw materials;

[0034] Step S3: Mix the α-sialon precursor powder with the remaining M2 source in the raw material to obtain a second mixture, sinter it in an inert atmosphere at 1750-2000° C. and 0.55-2 MPa, and grind it to obtain α-sialon phosphor.

[0035] According to the present application, the inventors have discovered that in the synthesis process of α-sialon phosphor, in addition to the fact that under high temperature and high pressure, due to the differences in temperature and pressure in the reaction system, impurities are easily produced, and the activation ions (M2 ions) are more difficult to dissolve into the crystal lattice than the matrix ions (M1 ions). Therefore, the crystal phase of the α-sialon phosphor obtained by direct synthesis is more difficult to control.

[0036] In the present application, α-sialon phosphor is synthesized in two steps. α-sialon precursor powder is obtained by sintering silicon nitride, aluminum source, M1 source and part of M2 source in an inert atmosphere at 1400-1700°C and 0.1-0.5MPa. α-sialon precursor powder containing a small amount of activating ions or no activating ions is synthesized under the above conditions. Since the gas pressure and temperature are relatively low, the temperature and gas pressure differences in the reaction system are relatively small. At the same time, partial addition or no addition of M2 source can effectively reduce the formation of impurities. Therefore, the α-sialon precursor powder has a better single-phase structure.

[0037] The above-mentioned α-sialon precursor powder is then mixed with most of the remaining M2 source as a precursor, and sintered in an inert atmosphere at 1750-2000°C and 0.55-2MPa. This is because although it is easier to obtain an α-sialon precursor with a single-phase structure under low temperature and low pressure conditions, the grains are not easy to grow further to obtain large-particle α-sialon with good crystallization, and smaller particles will affect the luminescence performance of the phosphor. Therefore, it is necessary to further crystallize and grow the α-sialon precursor powder as a seed under high temperature and high pressure. In this process, since the content of M2 ions in the α-sialon precursor powder is low and its radius is similar to that of the M1 ions, it is easier to dissolve into the unidirectional α-sialon without changing its phase composition, thereby obtaining large-particle α-sialon phosphor with a single-phase structure, and thus the α-sialon phosphor has good luminescence performance.

[0038] It should be noted that the above-mentioned M1 source and M2 source include but are not limited to the above-mentioned types. Those skilled in the art can select other known soluble elements according to actual needs. In addition, the method provided in the present application does not further limit the ratio of silicon and aluminum, and the ratio of oxygen and nitrogen in the α-sialon phosphor. Those skilled in the art can make adjustments according to actual needs to obtain α-sialon phosphors with different excitation wavelengths and generation wavelengths.

[0039] In some embodiments, the aluminum source includes aluminum nitride and / or aluminum oxide, M1 is Ca, and the M1 source includes calcium nitride and / or calcium carbonate; M2 is Eu, and the M2 source includes at least one of europium oxide, europium fluoride, europium nitride, europium boride, and europium oxynitride.

[0040] In some of the above embodiments, the specific types of aluminum source, M1 source, and M1 source are further defined. It can be understood that the above raw materials can be adjusted accordingly according to the composition of the target α-sialon phosphor. When the solid-dissolved matrix ions are calcium ions and the activating ions are europium ions, an α-sialon phosphor can be obtained that is excited in a wide wavelength range from ultraviolet to blue and emits yellow to orange light, which has a large application scenario.

[0041] In some embodiments, in step S2: the first mixture further includes a first flux, and the first flux is fluoride and / or chloride.

[0042] In some of the above embodiments, in step S2, by mixing the first flux into the first mixture, it is beneficial to increase the reaction activity, reduce the reaction temperature, reduce the generation of impurities, and the obtained α-sialon precursor powder has a better single-phase structure, so that the final α-sialon phosphor has a better luminescence effect. Preferably, the first flux is chloride.

[0043] It is understandable that the amount of the first flux added can be selected by those skilled in the art according to actual needs. As an example, the mass proportion of the first flux in the first mixture is 0.5% to 5%.

[0044] Fluorides include but are not limited to NH 4 F, LiF, NaF, KF, MgF 2 , CaF 2 , SrF 2 , BaF 2 , AlF 3 、Na 3 AlF 6 , K 3 AlF 6 , YF 3 At least one of; chlorides including but not limited to NH 4Cl, LiCl, NaCl, KCl, MgCl 2 , CaCl 2 、SrCl 2 、BaCl 2 、AlCl 3 , YCl 3 At least one of .

[0045] In some embodiments, in step S2: the sintering time is 2 to 6 hours.

[0046] In some of the above embodiments, the sintering time in step S2 is further limited, under which the reaction can be fully carried out to obtain an α-sialon precursor powder with a single-phase composition.

[0047] In some embodiments, in step S2: the average particle size of the α-sialon precursor powder is 1 to 5 μm.

[0048] In some of the above-mentioned embodiments, the average particle size of the α-sialon precursor powder obtained after crushing is 1 to 5 μm. At this time, the α-sialon precursor powder with a smaller particle size is more conducive to the growth of grains, and it is easier to obtain large particles of α-sialon phosphor with a single-phase composition. In addition, at this time, the α-sialon precursor powder has a larger specific surface area, which is more conducive to the solid dissolution of M2 ions into the grains, reducing the influence of its solid dissolution on the crystal phase, and is more conducive to obtaining an α-sialon phosphor with a single-phase composition, having better luminescence performance.

[0049] In some embodiments, in step S3: the second mixture further includes a second flux, and the second flux is fluoride and / or chloride.

[0050] In some of the above embodiments, in step S3, by mixing the second flux into the second mixture, it is beneficial to crystal growth and activation ion solid solution, making the grain size more uniform, and the obtained α-sialon phosphor has better luminescence effect. Preferably, the second flux is fluoride.

[0051] It is understandable that the amount of the second flux added can be selected by those skilled in the art according to actual needs. As an example, the mass proportion of the second flux in the second mixture is 0.5% to 5%.

[0052] In some embodiments, in step S3: the sintering time is 2 to 8 hours.

[0053] In some of the above embodiments, the sintering time in step S3 is further limited. Under this condition, the α-sialon precursor with a single-phase composition can be fully crystallized and grown to obtain large-particle, well-crystallized α-sialon phosphor, thereby having better luminescence performance.

[0054] In some embodiments, in step S2 and step S3, the inert atmosphere may be a nitrogen atmosphere.

[0055] In some embodiments, in step S3: after sintering, the material is kept warm at 1300-1600° C. and 0.05-0.1 MPa in a reducing atmosphere for 2-6 hours, wherein the reducing atmosphere is an inert gas with a hydrogen volume percentage of 1%-5%.

[0056] In some of the above embodiments, after sintering, heat treatment reduction can be performed under the above conditions. After this treatment, the single-phase α-sialon crystal can be made more stable, so that the obtained α-sialon phosphor has better luminescence performance.

[0057] In some embodiments, in step S3: the average particle size of the α-sialon phosphor is 10 to 30 μm.

[0058] In some of the above embodiments, when the α-sialon phosphor is crushed to an average particle size of 10 to 30 μm, it has better luminescence performance and is conducive to further processing and utilization.

[0059] It should be noted that the average particle size of the α-sialon phosphor has a well-known meaning in the art and can be detected by methods and instruments known in the art. As an example, it can be detected by using Mastersizer 3000 produced by Malvern Company with reference to GB / T19077-2016.

[0060] In some embodiments, in step S2: the mass of part of the M2 source accounts for less than 30% of the total mass of the M2 source in the raw material; preferably, no M2 source is added to the first mixture.

[0061] In some of the above embodiments, during the low-temperature and low-pressure synthesis of the α-sialon precursor powder in step S2, as little M2 source as possible or no M2 source is added, and during the high-temperature and high-pressure synthesis in step S3, all the remaining M2 source is added. This is more conducive to synthesizing an α-sialon precursor powder with a single-phase composition in step S2, and the α-sialon phosphor further synthesized thereby has better luminescence performance.

[0062] In some embodiments, the molar ratio of Si to Al in the α-sialon phosphor is 2 to 2.5.

[0063] In a second aspect, the present application provides an α-sialon phosphor prepared according to the method of any embodiment of the first aspect.

[0064] According to the present application, since the α-sialon phosphor is prepared by the method of any embodiment of the first aspect, the α-sialon phosphor has good luminescence performance.

[0065] In a third aspect, the present application provides a luminescent product comprising an α-sialon phosphor according to any embodiment of the second aspect.

[0066] According to the present application, since the luminescent product includes the α-sialon phosphor of any embodiment of the second aspect, the luminescent product has a better luminescent effect.

[0067] The scheme of the present application is described below in conjunction with the following specific examples. Unless otherwise specified, the raw materials used in the following examples are all from common commercial products, and the devices or equipment used are all purchased from conventional market sales channels, among which silicon nitride is from Ube Industries, E10 grade.

[0068] Emission spectrum test: Hangzhou Yuanfang LED phosphor relative brightness tester JY2003 is used for testing. The sample is made into a powder disk, and under the excitation of 450nm blue light wavelength, the emission spectrum is obtained by scanning the wavelength of 380~780nm through the spectrometer.

[0069] X-ray diffraction analysis: X-ray diffraction (XRD) instrument (Bruker D8 ADVANCE, Germany) was used to characterize the physical phase of the samples (the radiation source was Cu target Kα ray, tube voltage 40 kV, tube current 40 mA, λ = 0.15418 nm, step size 0.02°, scanning range 10°~90°).

[0070] Example 1

[0071] According to the composition formula Ca 1.77 Eu 0.08 Si 8.3 Al 3.7 (O 0.08 N 15.2 ), Ca was weighed in an anhydrous and oxygen-free glove box 3 N 2 28.97g, α-Si 3 N 4 122.98g, AlN 48.1g, europium oxide 0.66g.

[0072] In a sealed container, 28.97 g of Ca 3 N 2 、122.98gα-Si 3 N 4Mix with 48.1g AlN ball mill for 4h, then separate the ball to obtain the mixed raw material powder, put it into a boron nitride crucible, immediately place it in a carbon tube furnace, vacuum and heat at 600℃ for 2h, then fill with nitrogen, gas pressure 0.5MPa, heat to 1650℃ and keep warm for 4h. The powder block obtained after cooling is gently crushed and passed through a 100 mesh sieve to obtain small-particle α-sialon precursor powder with an average particle size of 2μm.

[0073] Weigh 30g of the powder, mix it with 0.66g of europium oxide and 0.3g of calcium fluoride as a flux, put it into a boron nitride crucible and place it in a carbon tube furnace, evacuate it and heat it at 600℃ for 2h, then fill it with nitrogen, the pressure is 1MPa, heat it to 1850℃ and keep it warm for 6h. After cooling, crush the powder block and pass it through a 100-mesh sieve, then ball mill it with water as a solvent for 20 minutes, then use 10% nitric acid to stir and wash it at 70℃ for 30 minutes, then dilute it with distilled water to neutral, filter it, and dry it at 120 degrees for 2 hours to obtain α-sialon phosphor.

[0074] The emission spectrum of the α-sialon phosphor was tested, and the emission peak wavelength was 598 nm.

[0075] The above-mentioned α-sialon precursor powder and α-sialon phosphor were subjected to X-ray diffraction analysis, and their XRD spectra were as follows: Figure 1 and Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that the α-sialon precursor powder and the α-sialon phosphor have the same single crystal phase structure, which also shows that the subsequent embedding of activation ions will not affect the original crystal phase structure.

[0076] The α-sialon precursor powder and the α-sialon phosphor were observed using a scanning electron microscope, and the scanning electron microscope images thereof are shown as follows: Figure 3 and Figure 4 As shown, from Figure 3 and Figure 4 It can be seen that the α-sialon precursor powder synthesized at low temperature and low pressure has a small grain size, and it further grows under subsequent high temperature and high pressure to obtain an α-sialon phosphor with a larger grain size.

[0077] Example 2

[0078] The preparation process is substantially the same as that of Example 1, except that 0.33 g of europium oxide and 0.39 g of europium fluoride are used instead of 0.66 g of europium oxide.

[0079] The emission spectrum of the α-sialon phosphor was tested, and the emission peak wavelength was 598.5 nm.

[0080] Example 3

[0081] The preparation process is substantially the same as that of Example 1, except that 0.79 g of europium fluoride is used instead of 0.66 g of europium oxide.

[0082] The emission spectrum of the α-sialon phosphor was tested, and its emission peak wavelength was 599 nm.

[0083] Example 4

[0084] The preparation process is substantially the same as that of Example 1, except that 0.62 g of europium fluoride is used instead of 0.66 g of europium oxide.

[0085] The emission spectrum of the α-sialon phosphor was tested, and its emission peak wavelength was 599 nm.

[0086] Comparative Example 1

[0087] According to the composition formula Ca 1.77 Eu 0.08 Si 8.3 Al 3.7 (O 0.08 N 15.2 ), Ca was weighed in an anhydrous and oxygen-free glove box 3 N 2 4.1g, α-Si 3 N 4 18.2g, AlN 7.1g, Eu 2 O 3 0.66g and 0.3g flux CaF 2 , mix evenly in a mortar, then put into a boron nitride crucible, immediately place in a carbon tube furnace, vacuum and heat at 600℃ for 2h, then fill with nitrogen, gas pressure 1MPa, heat to 1850℃ and keep warm for 6h. After cooling, crush the powder block and pass it through a 100-mesh sieve, then ball mill with water as solvent for 20 minutes, then use 10% nitric acid to stir and wash at 70℃ for 30 minutes, then dilute with distilled water to neutral, filter, and dry at 120 degrees for 2 hours to obtain α-sialon phosphor.

[0088] The emission spectrum of the α-sialon phosphor was tested, and the emission peak wavelength was 596 nm.

[0089] Comparative Example 2

[0090] According to the composition formula Ca 1.77 Eu 0.08 Si 8.3 Al 3.7 (O 0.08 N 15.2 ), Ca was weighed in an anhydrous and oxygen-free glove box 3 N 2 3.69g, α-Si 3 N 416.38g, AlN 6.39g, Eu 2 O 3 0.594 g, pre-synthesized Ca 1.77 Eu 0.08 Si 8.3 Al 3.7 (O 0.08 N 15.2 ) powder 3g as seed crystals, and 0.3g flux CaF 2 , mix evenly in a mortar, then put into a boron nitride crucible, immediately place in a carbon tube furnace, vacuum and heat at 600℃ for 2h, then fill with nitrogen, gas pressure 1MPa, heat to 1850℃ and keep warm for 6h. After cooling, crush the powder block and pass it through a 100-mesh sieve, then ball mill with water as solvent for 20 minutes, then use 10% nitric acid to stir and wash at 70 0C for 30 minutes, then dilute with distilled water to neutral, filter, and dry at 120 degrees for 2 hours to obtain α-sialon phosphor.

[0091] The emission spectrum of the α-sialon phosphor was tested, and the emission peak wavelength was 597 nm.

[0092] According to the emission peak wavelengths of the α-sialon phosphors obtained in Examples 1 to 4, α-sialon phosphors with different emission wavelengths can be obtained by adjusting the oxygen content in the raw material composition, indicating that this method is suitable for preparing α-sialon phosphors with different elemental compositions.

[0093] The emission spectra of the α-sialon phosphors in Example 1, Comparative Example 1 and Comparative Example 2 are as follows: Figure 5 ,according to Figure 5 It can be seen that the luminescence intensity of the α-sialon phosphor obtained by one-step high temperature and high pressure synthesis in Comparative Example 1 is the lowest, and the luminescence intensity of the α-sialon phosphor obtained by one-step synthesis by adding the pre-synthesized material as a seed in Comparative Example 2 is better than that of Comparative Example 1, but lower than that of Example 1. The luminescence intensity of the α-sialon phosphor obtained in Example 1 is better than that of Comparative Example 1 and Comparative Example 2, indicating that the α-sialon phosphor prepared using the method provided in the present application has better luminescence performance.

[0094] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing α-sialon phosphor, characterized in that: The following steps are involved: Step S1: According to the general structural formula M1 x M2 y (Si,Al) 12 (O,N) 16 The stoichiometric ratio of the composition provides silicon nitride, aluminum source, M1 source, and M2 source as raw materials, wherein M1 is selected from at least one of Li, Mg, Ca, Y, Sr, and Gd, and M2 is selected from at least one of Eu, Ce, Pr, Tb, Yb, Dy, and Er, 0.3≤x≤2.0, and 0≤y≤0.1; Step S2: mixing silicon nitride, aluminum source, M1 source and part of M2 source in the raw material to obtain a first mixture, sintering the mixture in an inert atmosphere at 1400-1700° C. and 0.1-0.5 MPa, and crushing the mixture to obtain α-sialon precursor powder; wherein the mass of the part of M2 source accounts for less than 50% of the total mass of the M2 source in the raw material; Step S3: Mix the α-sialon precursor powder with the remaining M2 source in the raw material to obtain a second mixture, sinter the mixture at 1750-2000° C. and 0.55-2 MPa in an inert atmosphere, and grind the mixture to obtain α-sialon phosphor.

2. The method according to claim 1, characterized in that The aluminum source includes aluminum nitride and / or aluminum oxide; the M1 is Ca, and the M1 source includes calcium nitride and / or calcium carbonate; the M2 is Eu, and the M2 source includes at least one of europium oxide, europium fluoride, europium nitride, europium boride, and europium oxynitride.

3. The method according to claim 1, characterized in that In the step S2: the first mixture also includes a first flux, and the first flux is fluoride and / or chloride.

4. The method according to claim 2, characterized in that: In the step S2: the sintering time is 2 to 6 hours.

5. The method according to claim 1, characterized in that In the step S2: the average particle size of the α-sialon precursor powder is 1 to 5 μm.

6. The method according to claim 1, characterized in that In the step S3: the second mixture also includes a second flux, and the second flux is fluoride and / or chloride.

7. The method according to claim 2, characterized in that In the step S3: the sintering time is 2 to 8 hours.

8. The method according to claim 1, characterized in that In the step S3: after the sintering, the temperature is kept at 1300-1600° C. and 0.05-0.1 MPa in a reducing atmosphere for 2-6 hours, wherein the reducing atmosphere is an inert gas with a hydrogen volume percentage of 1%-5%.

9. The method according to any one of claims 1 to 8, characterized in that: In the step S2: the mass of the part of the M2 source accounts for less than 30% of the total mass of the M2 source in the raw material; preferably, no M2 source is added to the first mixture.

10. An α-sialon phosphor, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

11. A luminous product, characterized in that: Including the α-sialon phosphor as described in claim 10.